PENETAPAN KADAR Pb PADA JAMU SERBUK ASAM URAT YANG DIJUAL DI PASAR TENGAH KOTA BANDAR LAMPUNG DENGAN METODE SPEKTROFOTOMETRI SERAPAN ATOM - Nurul Aini; Endang Sri Wahyuni (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2019)
THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND DIETARY COMPLIANCE OF CHRONIC RENAL FAILURE PATIENTS WITH HEMODIALYSIS THERAPY AT RSUD DR. H. ABDUL MOELOEKBackground: Chronic renal failure (CRF) is condition of decreased renal function gradually or completely. Hemodialysis usualy used as a therapy. There is an increasing number of CRF patients with hemodialysis therapy in Indonesia. Diet is an important factor for CRF patients, it can prevent or delay cardiovascular disease, prevent uremic poisoning and metabolic disorders.This study want to determine the relationship between family support (instrumental, informational, emotional and assessment) with dietary compliance of CRF patients with hemodialysis therapy.Methods: This was an analytical study with cross sectional design using family support as an independent variable and dietary as a dependent variable. This study using 78 hemodialysis patients at RSUD Dr. H. Abdul Moeloek, Lampung Province in 2016 as respondents.Results: Respondent’s characteristics of this study are mostly male (56.4%), age 41-60 years old (61.5%) with high school educational background (30.8%). The research show that respondents who have high family support (52,46%), with specification in high instrumental support (53.8%), low informational support (60.3%), low emotional support (57.7%), and low appraisal support (60.3%).The statistical test showed there was a significant relationship between instrumental support (p = 0.002), informational support (p = 0.002), emotional support (p = 0.030) and appraisal support (p = 0,000) with dietary compliance of hemodialysis patients. There was a significant relationship between family support and compliance of hemodialysis patiens at RSUD Dr. H. Abdul Moeloek in 2016 (p=0,000). It was suggested that we need to educate family member to improve the dietary compliance rate in hemodialysis patients.